2020
DOI: 10.48075/actaiguaz.v9i1.22327
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação in vitro da atividade fungitóxica de extratos de plantas contra Diplodia macrospora

Abstract: O fungo Diplodia macrospora é agente causal de doenças na cultura do milho, sendo responsável por diminuição da produção. Entre inúmeras formas de controle de doenças pode-se citar a utilização de extratos vegetais. Diante disto, o objetivo deste estudo foi verificar a ação do extrato de guaco, orégano, arruda, gengibre, penicilina, pulmonária, alecrim, eucalipto, romã e osmarin, contra D. macrospora. O ensaio foi realizado em delineamento interiramente casualisado sendo utilizado para cada extrato as concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Regarding the antifungal activity against Botryosphaeriaceae fungi, Matos et al [52] observed no inhibition of Lasiodiplodia theobromae for pomegranate oil at concentrations of up to 0.6%, but Lorenzetti et al [53] reported a significant inhibition (87%) of Diplodia macrospora at a concentration of 7.4% (i.e., at 74,000 µg•mL −1 ) of pomegranate peel extract. In comparison, the non-conjugated dwarf pomegranate fruit extract, for which an EC 90 of 4600 µg•mL −1 was estimated, should be much more effective (by a factor of 16).…”
Section: Comparison Of the Microbicidal Activity Of The Extractmentioning
confidence: 99%
“…Regarding the antifungal activity against Botryosphaeriaceae fungi, Matos et al [52] observed no inhibition of Lasiodiplodia theobromae for pomegranate oil at concentrations of up to 0.6%, but Lorenzetti et al [53] reported a significant inhibition (87%) of Diplodia macrospora at a concentration of 7.4% (i.e., at 74,000 µg•mL −1 ) of pomegranate peel extract. In comparison, the non-conjugated dwarf pomegranate fruit extract, for which an EC 90 of 4600 µg•mL −1 was estimated, should be much more effective (by a factor of 16).…”
Section: Comparison Of the Microbicidal Activity Of The Extractmentioning
confidence: 99%